KEANEKARAGAMAN DAN BIOAKTIVITAS SENYAWA AKTIF MAKROALGA PANTAI WEDIOMBO KABUPATEN GUNUNG KIDUL - Prasetyaningsih, Aniek; Rahardjo, Djoko (AgriSains, 2016)
Research of macroalga diversity and bioactivity was conducted from February to September 2016 at Wediombo beach, Gunung Kidul district. The used sampling method was â€œmetode jelajahâ€ and the environmental parameters measured include temperature, salinity, depth, pH, turbidity, dissolved oxygen (DO), and concentration of nitrate and phosphate. Identification was based on morphological characteristics. Extraction sample was stratified using ethanol and ethyl acetate. Method of HTS (High Throughput Screening) was applied to test the potential of active compounds. Antimicrobial Test was conducted with cell growth indicators (MTT), while the indicator DPPH was used for the antioxidant test (80mg / 100ml), and TLC and GC-MS for profiling the active compound. Seventeen species macroalgal were found at the shore of Wediombo, includes: Rhodophyta (7 species), Phaeophyta (5 species) and Chlorophyta (5 species) of which were dominated by macroalgal on coral reefs. Nine macroalgae found to have antioxidant activity (Acrocystis nana, Caulerpa sp., Chaetomorpha crassa, Dictyota sp., Gracilaria canaliculata, Gelidiella acerosa, Sargassum sp., Turbinaria sp. and Ulva lactuca) and 3 macroalgae (Boergesenia forbesii, Halymenia maculata and Palisada concreta ) did not possess the activity. Macroalgae which were tested for microbial activity, generally had antimicrobial against C. albicans and Shigella sonnei except E. coli. Results of TLC indicated that all of macroalgal had active compounds: terpenoid, glucose, flavonoids, phenols and amino acids but only few of them contained saponin, based on GC-MS test, Acrocystis nana, Zanardini was found to contain 1-Octadecyne (17.78%), Octadecanal (17, 83%) Dicholesteryl succinate (37.53%) and Cholestan-3-one, 4-methyl (26.86%) had the potential to be antimicrobial and antioxidant as well as bioenergy sources.Â Key words : Macroalga, High-Troughput Screening,Â  metabolites profiling